Mitigasi Bencana Dengan Pembuatan Plang Dan Piezometer Di Desa Pasiran Kabupaten Bengkalis - Arifudin Arifudin; Sopiatul Gadis Witri; Vilandra Oktavia; Arif Setiawan; Lia Sholihati; Lisa Efri Yeni; Nazliana Aqila; Carmella Yosfira; Sarah Junita Andriani Simanjuntak; Akhiyar Rofi; Erlando Fatiranes (FKIP, Universitas Palangka Raya, 2023)
Pasiran Village is a peat land area covering an area of 750.00 Ha. With the many negative impacts that will be caused by peatland fires, it is necessary to make preparedness efforts by making several evacuation route signs, fire-prone signs, and also making piezometers as a benchmark for awareness of peat water levels in the area. The method used is descriptive qualitative because it raises from the problems that occur in Pasiran Village, namely related to peatland problems and mitigation efforts. The gathering point area in Sandan Village is in Samikun Hamlet where the area is a fairly large field and is in the middle of residential areas. Burn-prone signs are installed around peatlands located adjacent to the plantations of Pasiran villagers. The piezometer made is a simple piezometer made from paralon and bamboo pipes. This effort is expected to provide benefits to the entire community of Pasiran Village.